Optimizing the Freedom Teaching Platform Application (PMM) Through the Cluster PAUD Learning Community - Jumarniati, Jumarniati; Fitriani, Fitriani (Pustaka Digital Indonesia, 2023)
Dedication program public this to give experience to Head Schools and PAUD Teachers in use independent platform application teach. Activity devotion done by the author Work The same Department of Education and Culture, City of Pare Pare. Problems main partners is an unprepared institution in accessing PMM applications and uses existing features inside. Objective from activity this is to share information related to the Merdeka Teaching Platform Application and participants capable access and complete topic as well as module until understanding method upload action real. Main partner in devotion This is Community Fostered PAUD Group Ujung sub district and sub district afternoon. Method accompaniment This consists of stage analysis needed partners, mentoring PMM optimization and evaluation achievement activity. Assistance results obtained that participants can access the Merdeka Mengajar Platform, have account study, do topics as well as existing modules in the PMM application as well know how to upload reports.